Hodnocení ekonomické výkonnosti podniku - Páleníková, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce se zaměřuje na hodnocení ekonomické výkonnosti podniku MR STEEL GROUP, s.r.o., na základě analýz účetních výkazů za sledované období 2012 – 2016. Ke zjištění ekonomické výkonnosti podniku jsem si vybrala finanční analýzu. Práce obsahuje textovou část a vypracovanou analytickou část, ve které je také představena společnost a návrhy na její zlepšení ekonomické situace. Dále srovnání s konkurentem obdobné velikosti.

The bachelor´s thesis focuses on the evaluation of the financial situation of the company MR STEEL GROUP, s.r.o. It is based on analysis of the financial statements from the years 2012 – 2016. To determinate the economic performance I have chosen the financial analysis. The thesis contains the theoretical part and the practical part. The practical part contains the introduction of the company, the analysis of the economic performance and the proposals for its improvements. The comparison of the company with the competitors of the same size is also included in the practical part.
Assesment of Economic Performance of Selected Company
Keywords: finanční analýza; finanční ukazatele; společnost; výkup; železo; kovový odpad; financial analysis; financial statements; company; repurchase; iron; metal trash